Property enhancement and mechanism of cement-based composites from the perspective of nano-silica dispersion improvement - Zhang, Tonghuan; Wang, Zhenjun; Wang, Wei; Li, Gang; Guo, Haoyan; Zhang, Haibao (Case Studies in Construction Materials, 2025)
Nano-silica (NS) exhibits significant potential for enhancing the properties of cement materials. However, its effectiveness in improving the properties of cement-based materials is hindered by the poor dispersion of NS within the cement matrix. In this work, the dispersibility of NS in cement solutions was improved by water reducers (FDN-C naphthalene water reducer and PCE-11 polycarboxylate superplasticizer) and mechanical dispersion methods (ultrasonication and magnetic stirrer), and their synergistic effects were investigated by ultraviolet visible spectrophotometry and zeta potential tests. Effects and mechanism of NS dispersibility on microstructure and properties of NS modified cement pastes (NS-C) were also investigated and analyzed. Results indicate that polycarboxylate superplasticizers have stronger adsorption on the surface of NS particles compared with naphthalene water reducers, which effectively improved the dispersion stability of NS in cement solutions. Furthermore, ultrasonication can ensure better dispersion of NS than magnetic stirrer. The synergistic effects of 1.0 % polycarboxylate superplasticizers and 1 h of ultrasonication enhances the dispersion of NS aggregates, thereby promoting the hydration reaction of cement and refining the pore structure. Additionally, this synergistic effect improves the workability and the compressive strength of NS-C. Thermogravimetric (TG) and industrial computed tomography (ICT) results indicated that the increase in C-S-H gel and the reduction in the volume of large pores (greater than 10 mm3) in NS-C dispersed synergistically with 1 % polycarboxylate superplasticizers and 1 h of ultrasonication are the mainly reasons for the improvement in compressive strength.